2006
DOI: 10.1002/dvdy.20737
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal cells with leukocyte and lymphendothelial characteristics in murine embryos

Abstract: The development of lymphatic endothelial cells (LECs) from deep embryonic veins or mesenchymal lymphangioblasts is controversially discussed. Studies employing quail-chick grafting experiments have shown that various mesodermal compartments of the embryo possess lymphangiogenic potential, whereas studies on murine embryos have been in favor of a venous origin of LECs. We have investigated NMRI mice from embryonic day (ED) 9.5 to 13.5 with antibodies against the leukocyte marker CD45, the pan-endothelial marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 28 publications
3
54
0
Order By: Relevance
“…Although our results show that developing lymphatic vasculature arises mostly from venous-derived Prox1-expressing progenitor cells, two recent reports have claimed that other cell types contribute to developing lymphatics in mice. Buttler et al (2006) proposed that scattered mesenchymal cells with leukocyte and lymphoendothelial characteristics that are first detected after E10.5 eventually integrate into the lymphatics. Sebzda et al (2006) identified a subpopulation of Syk-and Slp-76-expressing hematopoietic-derived CEPs that acquire a lymphatic fate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although our results show that developing lymphatic vasculature arises mostly from venous-derived Prox1-expressing progenitor cells, two recent reports have claimed that other cell types contribute to developing lymphatics in mice. Buttler et al (2006) proposed that scattered mesenchymal cells with leukocyte and lymphoendothelial characteristics that are first detected after E10.5 eventually integrate into the lymphatics. Sebzda et al (2006) identified a subpopulation of Syk-and Slp-76-expressing hematopoietic-derived CEPs that acquire a lymphatic fate.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that venous identity is required for embryonic lymphangiogenesis and that Prox1-expressing venous ECs are the main source of LECs in the developing mammalian embryo. However, a contribution of hematopoietic-derived LEC progenitors to the developing lymphatics has also been suggested (Buttler et al 2006;Sebzda et al 2006). Therefore, we further addressed whether hematopoieticderived LECs (lymphangioblasts) contribute to the mammalian embryonic lymphatic vasculature in another mouse model.…”
Section: Lymphatic Vasculature Is Venous Derived Genes and Development mentioning
confidence: 98%
See 1 more Smart Citation
“…Even in mice deficient for the transcription factor Runx1, which show severely impaired hematopoiesis during development and die in utero, primitive lymph sacs develop normally (Srinivasan et al 2007). Reports describing mesenchymal cells with macrophage and LEC characteristics within and around developing murine lymphatic vessels nourish the speculation that also in mammals, there may be a dual origin of the lymphatic vascular system (Buttler et al 2006(Buttler et al , 2008. However, functional inactivation of the Prox1 transcription factor in cells derived from the venous endothelium severely impairs lymph sac development, suggesting that Prox1-expressing venous endothelial cells are the main source of LECs during lymphatic vasculature development in the mouse (Srinivasan et al 2007).…”
Section: The Interrelationship Of Lymphatic Endothelium and Hematopoimentioning
confidence: 99%
“…In Xenopus tadpoles, PROX1-positive mesodermal precursor cells, lymphangioblasts, which share a common origin with vascular progenitor cells, contribute to lymphatic vessel formation (Ny et al 2005). In murine embryos, scattered mesenchymal cells, which coexpress leukocyte (CD45) and lymphatic endothelial markers (LYVE-1, PROX1), were detected in the regions of new lymphatic vessel growth; and it was suggested that the triple positive cells (LYVE-1 + , PROX1 + , F4/80 + ) with characteristics of LECs and macrophages may integrate into lymphatic vessels (Buttler et al 2006(Buttler et al , 2008a. The functional role of such cells remains unclear, as formation of lymph sacs is not aVected in Runx1 ¡/¡ mice, which have defective hematopoiesis, and lineage tracing studies failed to demonstrate contribution of hematopoietic cells to lymphatic endothelium up to the embryonic day E16.5 (Buttler et al 2008b;Srinivasan et al 2007).…”
Section: Embryonic Development Conceptsmentioning
confidence: 99%